Perhitungan Value at Risk Pada Portfolio Optimal: Studi Perbandingan Saham Syariah dan Saham Konvensional - Heryanti, Sri Astuti (IKONOMIKA, 2017)
The aim of this study was to obtain empirical evidence about the difference between the level of risk when investing stocks in the Islamic and conventional by using Value at Risk (VaR). The object of research including consistent stock in the Jakarta Islamic Index and LQ45. The analytical method used in this research is quantitative analysis consisting of the establishment of the optimal portfolio by Markowitz method, calculation of VaR and testing the differences with Independent sample t-test. This study indicated that the value every stock can be reduced by diversifying through the establishment of an optimal portfolio. Based on the calculation Independent sample t-test, it is known that there is no difference between VaR of Islamic stocks and conventional stocks.